THE EFFECT OF INFORMATION TECHNOLOGIES IN ARCHITECTURAL SHAPING APPROACHES: GENERATIVE SHAPING APPROACHES - CANBEYLİ, Yelda; ÖZEN YAVUZ, Arzu (SSD Journal, 2018)
Architecture; beyond its social, economic and technological usage is concerned with designing spaces and shaping objects. How architects begin the process of design and which methods they employ is a considerable research interest. This study has evaluated some of the generative design methods used for architectural design. This topic was investigated through the lens of architectural design contests held over the Turkey in the 21st century, a time when design methods have recently been bolstered by advancing information and technology networks. Decision-making processes of generative design approaches from architecture contests were analysed and factors and approaches influencing design were attempted to be found.